The effect of ovarian injection of autologous platelet rich plasma in patients with poor ovarian responder: a systematic review and meta-analysis - Li, Xuanling; Liu, Huicong; Lin, Guangyao; Xu, Lianwei (Frontiers in Endocrinology, 2023)
Objective：To evaluate the effects of ovarian injection of autologous platelet rich plasma (aPRP) on patients with poor ovarian responder (POR) based on the existing clinical evidence.Methods: According to systematic review and meta-analysis, we comprehensively searched nine databases established as of September 6, 2023, and evaluated the impact of ovarian PRP infusion on poor ovarian responder.The research results include serum follicle-stimulating hormone(FSH) and anti-Mullerian hormone(AMH) levels, antral Follicle Count(AFC), oocyte number, and embryo number. The Newcastle Ottawa Scale (NOS) was used to evaluate the quality of inclusion in trials.Results: Add up to 10 studies consisting of 793 participants were included in the meta-analysis. A review of existing evidence showed that intraovarian injection of PRP has significant therapeutic effects in increasing levels of anti-Müllerian hormone (AMH) (SMD=0.44,95% CI [0.07,0.81], p=0.02), antral follicle count (AFC) (MD=1.15,95% CI [0.4,1.90], p=0.003), oocyte count (MD=0.91, 95% CI [0.40, 1.41], p=0.0004), and embryo number (MD=0.78, 95% CI [0.5,1.07], p<0.0001). We compared the relevant data of patients before and after treatment after 2 months of intervention. It can be seen that ovarian injection of PRP treatment for 2 months has better effects in reducing FSH levels, increasing AMH levels, increasing antral follicle count, and increasing the number of oocytes and embryos (p<0.05). When the dose of PRP injected into each ovary was ≥ 4ml, there was also a significant correlation (p<0.05) with improving the number of AFC, oocytes and embryos. Significant heterogeneity existed among the studies.The pooled results suggest that intra-ovarian injection of PRP can promote ovarian regeneration and improve the reproductive outcomes of patients with ovarian dysfunction. This therapy may have significant clinical potential in improving sex hormone levels, increasing AFC, oocyte count, and embryo count. However, this findings still requires more rigorous and extensive trials worldwide to determine the value of intra-ovarian injection of PRP in POR patients.System review registration: Registered in https://www.crd.york.ac.uk , and the identifier is CRD42023451232.